Generating high spectral consistent endurance time excitations by a modified time-domain spectral matching method. Issue 145 (June 2021) - Zhang, Ruifu; Zhang, Luqi; Pan, Chao; Chen, Qingjun; Wang, Yanchao
Abstract: Endurance time acceleration functions (ETAFs) are the intensified acceleration time series whose spectral responses match time-varying targets in order to evaluate multiple-level structural seismic performances with few dynamic analyses. However, the matching precision of the ETAFs generated by the existing frequency-domain method is not satisfactory enough and thus still needs three or more ETAFs to reach an acceptable accuracy. In this study, a high-precision and efficient ETAF generation method is proposed to obtain highly spectral consistent ETAFs. Considering the time-varying characteristic of ETAFs, the time-domain spectral matching technique is modified and extended to improve the spectral fitness of ETAFs for multiple durations. Taking the multi-duration response spectra as the matching targets, the matching procedure is conducted, and several ETAFs are generated in accord with seismic design codes. The matching precision is controlled by a specified tolerance and the number of iterations. The results show that the proposed method can successfully generate high-accuracy ETAFs, so that a sufficient accuracy of seismic performance analysis can be reached with only one single ETAF. The ETAFs generated by the proposed method are compared with those generated by an existing method in the matching precision, computational time, time variation trend, and the ETAF duration. Compared with the existing method, the proposed method can achieve remarkably higher matching precision and requires considerably less computational time, especially for long-duration ETAFs. The proposed method can also match average acceleration spectra from real ground motions and accurately predict the seismic responses in the structural nonlinear analysis. Highlights: An ETAF generation method based on time-domain spectral matching was proposed. Time-domain spectral matching method is modified and extended to consider multiple durations. The matching precision was remarkably improved, and the computation time was reduced. The effect of the number of subseries on the matching precision and computational time of the proposed method was investigated. The improved precision and efficiency for long-duration and short-duration ETAFs were compared.